Land survey for research stations: IITA research guide, No. 1 - Couper, D.C. (1991)
In agriculture, surveying is required to prepare topographical maps that indicate variations in the level of the land's surface. Topographical maps are necessary as a base for the preparation of research station maps which include layout of field, buildings, roads, and soil conservation measures.